Optimization Of Early Detection Coverage of Non-Communicable Diseases (NCD) At The Ngadiluwih Health Center UPTD, Kediri Regency - Agusta Dian Ellina; kurnia, kurnia eka permana; Meylany Rosa Puspita (Journal of Community Engagement in Health, 2025)
This community service activity aims to improve the skills of health cadres in optimizing the coverage of early detection of non-communicable diseases using the SAKTI application at the Ngadiluwih Health Center UPTD, Kediri Regency. Non-communicable diseases have increased every year and are one of the leading causes of death, which is of national and global concern at this time. Based on the results of a preliminary study at the Ngadiluwih Health Center in 2023, it was found that the non-communicable disease control program in 2023 had not reached the target; therefore, it was necessary to strengthen the Primary Service Integration (ILP) at the Ngadiluwih Health Center, Kediri Regency. The data collection method used a questionnaire that was administered before (Pre-test) and after (post-test) the implementation of the activity. The results of the statistical analysis showed a significant increase in knowledge and skills. The average pre-test value was 6.23, and the average post-test value increased to 8.88. The significance value of the Wilcoxon Test was 0.000 (p <0.05), which indicated that the increase in knowledge and skills was statistically significant.  This increase indicates that the counseling method carried out successfully increased the knowledge and skills of cadres on the use of the SAKTI Application, and they were able to conduct independent screening in the community.